Metaphor and meaning in psychotherapy - Siegelman, Ellen (New York Guilford Press, 1990)
When therapists hear patients talk of feeling "imprisoned," "burning with rage," "trapped," or "unequipped," they are witnessing manifestations of the symbolic attitude, the hallmark of all depth psychology. Most clinicians naturally respond to and use metaphors, but they often fail to understand the full potential of metaphoric images. This volume, in addressing the transforming power of metaphor, demonstrates how clinicians can deepen the therapeutic encounter.
Includes bibliographical references (pages 185-191) and index.
Keywords: Metaphor -- Therapeutic use; Symbolism (Psychology); Psychotherapy